Pengaruh Digital Payment ShopeePay dan Locus Of Control terhadap Perilaku Konsumtif Mahasiswa - Fitrianova Andriani, Beid; Diniah, Zahratud; Rosmanidar, Elyanti (Indonesian Journal of Islamic Economics and Business, 2023)
Consumptive behavior is excessive buying behavior by prioritizing secondary and tertiary needs rather than primary needs which causes a person to be extravagant. This study aims to determine whether there is influence of digital payment ShopeePay and locus of control on the consumptive behavior of students of the Islamic Economics and Business Faculty. The population of this study were students of the Faculty of Islamic Economics and Business, UIN Sulthan Thaha Saifuddin Jambi class of 2019, the number of research samples was 85 students using a purposive sampling technique by selecting students who used digital payment ShopeePay. The data collection method in this study uses a questionnaire. Variable data were analyzed using multiple linear regression. The theory used in this research includes; Digital Wallets, Personality Psychology, Consumer Behavior, and Consumptive. The results of the study show that simultaneously digital payment ShopeePay and locus of control have a positive and significant effect on consumptive behavior. Partially, digital payment ShopeePay has a positive and significant effect on consumptive behavior. Locus of control does not affect consumptive behavior. Based on the data analysis in this study, these variables are valid and reliable. In testing the classical assumptions with normal distribution there is no heteroscedasticity and multicollinearity.